Factors Associated With Occupational Commitment of Secondary School Teachers in Kuala Lumpur - Khamis Ali, Ali (2002)
This research was an attempt to study factors associated with the occupational commitment of secondary school teachers in Kuala Lumpur, Malaysia. The research design was a descriptive correlational study and the data were collected using questionnaires. The study followed a survey method which used a stratified sampling technique to select 510 teachers. A response rate of 83 .23% (433) was considered to be valid. Both descriptive and inferential statistics were used to analyse the data of the study. The research findings showed that teachers' levels of affective, continuance, normative and overall occupational commitment were moderate. Female teachers indicated higher affective, normative and overall occupational commitment than did males. Malay teachers indicated higher affective and overall occupational commitment than did teachers from Chinese, Indian and other ethnic groups. Both non-graduate teachers and teachers with a Bachelor's degree showed higher affective, continuance, nonnative and overall occupational commitment than did teachers with a Master' s degree. Years of experience in a current school had a significant correlation with continuance occupational commitment; whereas number of children had a significant correlation with overall occupational commitment. furthermore, the findings showed that supportive principal behaviour, engaged teacher behaviour, frustrated teacher behaviour, affective organizational commitment, continuance organizational commitment, normative organizational commitment, role conflict, intrinsic motivation and extrinsic motivation have significant correlations with affective, continuance, nonnative and overall occupational commitment. Role ambiguity has a significant correlation with affective, normative and overall occupational commitment. Intimate teacher behaviour has a significant correlation with only affective occupational commitment.